PERGESERAN MAKNA PAHLAWAN DI KALANGAN REMAJA:: SEBUAH TA NTA NG AN PENDIDIKAN - EFIANINGRUM, ARIEFA (FOUNDASIA, 2005)
The rapid development of Information and Communication Technology has cultural implications in society. The agenda setting theory, states that media determine people's way of thinking. The agenda setting theory states that media determine people's way of thinking. Due to the strong penetration of media, configures have begun to replace old ones. Media continuously offer a new status, making the popularity oj contemporary heroes more and more significant. As a reference group, heroes are figures with whom the young generation identify themselves. A hero with its conventional meaning is alwavs changing. Formerly, a hero was a figure with an exceptionally charming personality. Nowadays. media have a role to set new objects that the puhhe admire through pseudo-heroism. This is called the involution of the meaning qf heroism. Such a phenomenon becomes a challenge in the field of education to re-actualize the meaning ofa real hero, namely a conscientious hero.